ANALISIS PERHITUNGAN ULANG LAMPU PENERANGAN JALAN BYPASS NGURAH RAI - Andre Agusta Putra, Gede; Wijaya, I Ketut; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i04.p16, 2020)
Public Street Lighting is a facility needed as a navigation aid for road users, increasing the safety and comfort of road users, and supporting environmental security. The lack of lighting on the Ngurah Rai Bypass road is then performed a recalculation analysis and replacing the existing lamps with LED types in order to maximize the lighting contained in the Ngurah Rai Bypass. Measurements are made starting from the intersection of the Bali Mandara Toll road traffic lights towards (East) Sanur which ends at the first traffic light after the Bali Mandara Toll traffic light, this road is an Arterial type road with a road width of 8 meters with a road length of 1270m. The method used in this research is descriptive quantitative, that is, data collection is done through measurement using objective and standard tools. The calculation results are then compared with the conditions that occur in the field using IBM SPSS Statistics. Based on the results of the research, it shows that the lamps installed with 10.21 lux still do not meet SNI 11- 20 lux. Changing the type of mercury lamp to a 120 Watt LED lamp produces 13.21 lux, which meets SNI for PJU lighting.